2012
DOI: 10.1021/np300386d
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ Agonist from Chromolaena odorata

Abstract: A phytochemical investigation of Chromolaena odorata resulted in the isolation of five new compounds, 5aα,6,9,9aβ,10-pentahydro-10β-hydroxy-7-methylanthra[1,2-d][1,3]dioxol-5-one (1), 1,2-methylenedioxy-6-methylanthraquinone (2), 3-hydroxy-1,2,4-trimethoxy-6-methylanthraquinone (3), 3-hydroxy-1,2-dimethoxy-6-methylanthraquinone (4), and 7-methoxy-7-epi-medioresinol (5), together with 12 known compounds, odoratin (6), 3β-acetyloleanolic acid (7), ursolic acid (8), ombuin (9), 4,2'-dihydroxy-4',5',6'-trimethoxyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Our study provided compelling evidence that UA activated PPARγ; this finding was consistent with the previous observation that UA isolated from Chromolaena odorata acts as PPARγ agonist. 33 In addition, BADGE, a PPARγ antagonist, abolished the agonistic effect of UA on PPARγ. Co-treatment with UA and BADGE resulted in PPARγ levels similar to the control levels, and the changes in MMP2, MMP9, and TIMP1 expression were significantly diminished by BADGE co-treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Our study provided compelling evidence that UA activated PPARγ; this finding was consistent with the previous observation that UA isolated from Chromolaena odorata acts as PPARγ agonist. 33 In addition, BADGE, a PPARγ antagonist, abolished the agonistic effect of UA on PPARγ. Co-treatment with UA and BADGE resulted in PPARγ levels similar to the control levels, and the changes in MMP2, MMP9, and TIMP1 expression were significantly diminished by BADGE co-treatment.…”
Section: Discussionmentioning
confidence: 98%
“…The proton at The NOESY experiment revealed a correlation between H-8 and 7′ which indicates the Z geometry of the double bond [17]. The HMBC spectrum showed the methoxy proton at δ 3.78 correlated Table 1 1 H NMR (400 MHz) and 13 C NMR (100 MHz) spectral data of compounds 1-3 (δ in ppm). with C-9 (δ 171.7), which confirmed the ester moiety.…”
Section: Structural Determinationmentioning
confidence: 93%
“…Chemical structures of all compounds. [11,12], (+)-medioresinol (5) [13], (+)-syringaresinol (6) [13], (+)-6-(4-hydroxy-3-methoxyphenyl)-3,7-dioxabicyclo [3.3.0]octan-2-one (7) [11], coumarin (8), 8-hydroxycoumarin (9), 5-hydroxycoumarin (10), 7-hydroxycoumarin (11), 4-hydroxybenzaldehyde (12), and vanillin (13).…”
Section: Structural Determinationmentioning
confidence: 99%
“…The leaves of C. odorata also contain the highest concentration of allelochemicals isolated from a plant (98). A study in Vietnam revealed that the aqueous extract of the leaf contained flavonoids (salvigenin, sakuranetin, isosakuranetin, kaempferide, betulenol, 2-5-7-3 tetra-o-methyl quercetagetin, tamarixetin, two chalcones and odoratin and its alcoholic compound), essential oils (geyren, bornyl acetate and β-eubeden), saponin triterpenoids, tannins, organic acids and numerous trace substances (99). Another study by Heiss et al (100)…”
Section: Chemical Constituents Of Chromolaena Odoratamentioning
confidence: 99%